Challenges facing commercial farmers in an inflationary environment in Zimbabwe - Chipfunde, Alexio (My University, 2010)
Refer to document
Thesis (MBA. (Business Administration)) -- University of Limpopo, 2010
Keywords: Commercial farmers; Zimbabwe; Farm income -- Zimbabwe; Farm corporations -- Zimbabwe; Farm law -- Zimbabwe; Farm supply industries